Sustainable knowledge integration: Enhancing green development resilience - Jingfeng Huang; Bai Yang; Bing Zhou; Bing Ran (Journal of Innovation & Knowledge)
The revised Environmental Protection law (NEPL), enacted in 2015, introduced stricter regulations to address environmental challenges and promote sustainable development. This study investigated the law's impact on enterprise green development resilience (EGDR) through a novel integration of institutional and resource-based theories. Employing the Vertical and Horizontal Slot-Drawing (VHSD) and entropy methods, we developed a comprehensive framework to systematically measure EGDR, capturing both dynamic and structural aspects of resilience. Our findings revealed that, from an institutional perspective, compliance with environmental laws enhances corporate legitimacy and fosters green development. Meanwhile, the resource-based view highlighted how NEPL improves EGDR by promoting green knowledge, stimulating green innovation, offering policy incentives, and easing financial constraints. Notably, the law's effectiveness varies across regions and technological contexts, underscoring significant heterogeneity. These findings uncovered previously unexplored mechanisms linking environmental law enforcement and enterprise resilience, providing actionable insights for policymakers to design more effective environmental strategies. This study contributes to sustainable development research by advancing the understanding of how regulatory frameworks shape green resilience, offering a new lens to examine the interplay between environmental governance and business sustainability.